Implications of spicule activity on coronal loop heating and catastrophic cooling. Issue 4 (13th November 2021) - Nived, V N; Scullion, E; Doyle, J G; Susino, R; Antolin, P; Spadaro, D; Sasso, C; Sahin, S; Mathioudakis, M
ABSTRACT: We report on the properties of coronal loop foot-point heating with observations at the highest resolution, from the CRisp Imaging Spectro-Polarimeter located at the Swedish 1-m Solar Telescope and co-aligned NASA Solar Dynamics Observatory observations, of Type II spicules in the chromosphere and their signatures in the extreme ultraviolet (EUV) corona. Here, we address one important issue, as to why there is not always a one-to-one correspondence, between Type II spicules and hot coronal plasma signatures, i.e. beyond TR temperatures. We do not detect any difference in their spectral properties in a quiet Sun region compared to a region dominated by coronal loops. On the other hand, the number density close to the foot-points in the active region is found to be an order of magnitude higher than in the quiet Sun case. A differential emission measure analysis reveals a peak at ∼5 × 10 5 K of the order of 10 22  cm −5  K −1 . Using this result as a constraint, we conduct numerical simulations and show that with an energy input of 1.25 × 10 24 erg (corresponding to ∼10 RBEs contributing to the burst) we manage to reproduce the observation very closely. However, simulation runs with lower thermal energy input do not reproduce the synthetic AIA 171 Å signatures, indicating that there is a critical number of spicules required in order to account for the AIA 171 Å signatures in the simulation. Furthermore, the higher energy (1.25 × 10 24 erg) simulations reproduce catastrophic cooling with a cycle duration of ∼5 h, matching a periodicity we observe in the EUV observations.